IMPLEMENTASI PROGRAM UNIVERSAL COVERAGE DALAM PELAYANAN KESEHATAN DI RUMAH SAKIT PROF. DR. R. D. KANDOUW MANADO - Runtunuwu, Vega Alfa; Mandey, Jantje; Dengo, Salmin (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : Since 2011 the municipality of Manado implement programs or Universal CoverageUniversal Health Insurance, which is the social protection program in the field of public health to ensurethe city of Manado who do not have health insurance. in respect of it, this research to know "how theuniversal coverage program implementation in health care in hospitals. Prof. Dr. RD Kandou Manado.Research using qualitative methods. in this case the universal coverage programimplementation seen / observed by using the four critical variables in the model of implementation of thepolicy of Edward III, Communications, Resources, Disposition, and Bureaucratic Structure. informants inthis study were taken from: Program Implementation Unit (4 people), Dr Kandou (4 people) andCommunity (4 people). Data collection with interactive model analysis techniques of Miles andHubernam.The results showed: (1) Communication between the program managers, health careproviders and community groups performed well targeted and effective; (2) HR and financial resourcesfor adequate implementation provided; (3) Disposition (commitment and consistency) implementprograms and health care providers are good / high; and (4) The bureaucratic structure well ordered andeffective.Based on these results it can be concluded that the implementation of universal coverage(Jamkesta) in health care at the Hospital Prof. Dr. RD Kandou run properly and effectively see the factorof communication, resources, disposition and bureaucratic structure.Conclusions based on these results suggested still need to improve the implementation of the universalcoverage program to make it better.Keywords : implement programs or Universal Coverage Universal Health Insurance